Triple jump drills - Lomax, T. (The Best of British Track & Field Drills Series, 2009)
2X UK Olympic Team Coach, 3X World Championship Coach and current UK National Event Coach Terry Lomax shares with you his fundamental triple jump skills and triple jump drills. Lomax includes several proven progressions to help your athletes jump higher and further than they ever have before. He starts with basic continuous warm-up drills that include jogging, skipping, hoping, directional lunges and body movement exercises to help reduce the chances of injury during practice and meets. Lomax's teaching principles focus on good posture and rhythm, and he shows several strategies for all levels of track to keep your athletes bounding and jumping "Tall." The video will provide you with several new triple jump drills that work on the three phases of the jump, and how to correct common errors by young jumpers. Coach Lomax and his drill series make this a must see video for all coaches.